Frailty and medical financial hardship among older adults with cancer in the United States - Lao, Jiahui; Su, Mingzhu; Zhang, Jiajun; Liu, Li; Zhou, Shengyu; Yao, Nengliang (Frontiers in Oncology, 2023)
Background Little is known about the association between frailty level and medical financial hardship among older adults with cancer. This study aims to describe the prevalence of frailty and to identify its association with medical financial hardship among older cancer survivors in the United States. Methods The National Health Interview Survey (NHIS; 2019–2020) was used to identify older cancer survivors (n = 3,919). Both the five-item (Fatigue, Resistance, Ambulation, Illnesses, and Low weight-for-height) FRAIL and the three-domain (Material, Psychological, and Behavioral) medical financial hardship questions were constructed based on the NHIS questionnaire. Multivariable logistic models were used to identify the frailty level associated with financial hardship and its intensity. Results A total of 1,583 (40.3%) older individuals with cancer were robust, 1,421 (35.9%) were pre-frail, and 915 (23.8%) were frail. Compared with robust cancer survivors in adjusted analyses, frail cancer survivors were more likely to report issues with material domain (odds ratio (OR) = 3.19, 95%CI: 2.16–4.69; p < 0.001), psychological domain (OR = 1.47, 95%CI: 1.15–1.88; p < 0.001), or behavioral domain (ORs ranged from 2.19 to 2.90, all with p < 0.050), and greater intensities of financial hardship. Conclusion Both pre-frail and frailty statuses are common in the elderly cancer survivor population, and frail cancer survivors are vulnerable to three-domain financial hardships as compared with robust cancer survivors. Ongoing attention to frailty highlights the healthy aging of older survivors, and efforts to targeted interventions should address geriatric vulnerabilities during cancer survivorship.